Modern concept of treatment of biliary peritonitis complicated by abdominal sepsis (Review of the literature) - O. A. Tereshchenko; A. A. Botashev; Yu. V. Pomeschik; E. A. Petrosyan; V. I. Sergiyenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze and generalize the information on up-to-date treatment of the biliary peritonitis complicated by abdominal sepsis.Key points. The urgency of this issue is caused by its high frequency in postoperative period in patients with gallstone disease. Options of the newest methods of treatment of biliary peritonitis complicated by abdominal sepsis are analyzed. Features of each method in algorithm of essential medical actions are stressed.Conclusion. According to analysis, that was carried out, application of combined treatment of biliary peritonitis complicated by abdominal sepsis, is the only correct decision. The further improvement of treatment methods will promote achievement of the best results.